The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1111/j.1439-0434.2006.01066.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Tospovirus Incidence and Thrips Populations on Tomato in Mendoza, Argentina

Abstract: The objectives of this work were to estimate the capability of local populations of thrips as vectors of groundnut ringspot virus (GRSV) and tomato spotted wilt virus (TSWV), and to determine the species composition of vectors in tomato crops. Transmission assays were performed. Incidence of tospoviruses was estimated in commercial crops. Random samples of flowers were taken from tomato for identification of thrips. Of the five species of thrips tested, Frankliniella gemina (first record), F. occidentalis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…These results indicate that F.occidentalis has replaced and possibly competitively displaced F. australis as the most common species. de Borbon et al (2006) reported that F. occidentalis was more common than F. australis on crop and wild plant species in Argentina.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that F.occidentalis has replaced and possibly competitively displaced F. australis as the most common species. de Borbon et al (2006) reported that F. occidentalis was more common than F. australis on crop and wild plant species in Argentina.…”
Section: Discussionmentioning
confidence: 99%
“…Frankliniella schultzei transmits a virus causing a tanning feature in the leaves of tomatoes and a curving in the pointer plant. When the virus is installed in the fruit, the symptoms consisted of concentric rings, both in green as well as mature fruits 6 . In Brazil, the damages caused by the virus on tomato production can lead to reductions of 20 to 70 % of crop losses as well as reduce the production of flowers and fruit around 85 % 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Frankliniella schultzei Trybon (Thysanoptera: Thripidae) is an insect that causes direct damage by feeding on leaves and indirect damage due to its capacity to transmit the Groundnut ring spot virus (GRSV) (Borbón et al 2006) and Tomato spotted wilt virus (TSWV) (Coutts and Jones 2005), which can make tomato production unviable (Tedeschi et al 2001).…”
Section: Introductionmentioning
confidence: 99%